Reconstruire des châteaux au xxe siècle ? - Fanny Crozet (In Situ)
This article is an analysis of the processes involved in rebuilding the castles and stately homes of the present-day Nouvelle-Aquitaine region after the Second World War. It hopes to renew the history of this second reconstruction in France in two separate directions. First of all, it looks at a region that has been little examined from the point of view of reconstruction history, with the notable exception of the towns of Royan and Oradour-sur-Glane. Secondly, it identifies what might be called a blind spot in existing studies of the reconstruction, concerning an architectural type which is isolated and broadly scattered, and not mentioned in the reconstruction planning documents (PRA) generally studied. We examine the way this building type was integrated into the phenomenon of reconstruction by adapting to the material context of the second reconstruction and also to its economic context. It tries to understand how the age-old architecture of the buildings was renewed in order to accommodate notions as prosaic as economy and rationalisation, hitherto foreign to it. Based on a study corpus of about fifty sites, it takes a detailed look at the rebuilding processes undertaken both on the ‘minor’ heritage of damaged buildings, which did not benefit from any measure of historic monument protection, and at the more significant heritage of castles or stately homes which were protected (classés) as historic monuments. From out of the shadows of the architectural programmes for destroyed cities, a new kind of heritage thus emerges, conditioned by the economic constraints and new requirements of contemporary times.